"I am a lefty in a right‐handed world": Qualitative analysis of clinical learning experience of left‐handed undergraduate dental students. (22nd February 2019) - Al Lawati, Imad; Al Maskari, Hind; Ma, Sunyoung
Abstract: Background: Left‐handedness is the preferential use of the left hand in single‐handed activities such as writing. There are many studies in the literature on left‐handedness in relation to professional sports, medicine and surgery. Although dentistry largely depends on manual dexterity and hand skills, there has been little research to investigate the effect of left‐handedness on clinical dentistry, particularly in Australasia. Aim: To gain an insight into the clinical learning experience of left‐handed undergraduate dental students at the Faculty of Dentistry, University of Otago, New Zealand. Methods: Purposive sampling of left‐handed students was done within the final‐year class of undergraduate dental students, and they were invited to participate in a semi‐structured group interview to discuss their clinical learning experience at the Faculty. Six participants agreed to participate, and the interview was recorded and transcribed verbatim. Collected data were analysed using a thematic inductive/interpretive analysis approach according to the constructivist grounded theory. Results: All participants reported having clinical difficulties being left‐handed students learning using right‐handed equipment. There was a common theme of experiencing hand and wrist musculoskeletal problems as well as feeling of guilt causing patient discomfort during treatment. The majority of participants reported incidents where they were told by their supervisors to learn practising dentistry with their right hand and they felt that little guidance was given on how to operate as a left‐handed clinician. All participants perceived that being a left‐handed operator affected their efficiency and confidence level in their early clinical years. Conclusion: Left‐handed students have a strong sense of adaptability. However, in order to improve the learning experience regardless of the difference in the operator's preference of dominant hand, students should be provided with appropriate equipment such as ambidextrous dental chairs and professional guidance, especially during their early career.